BAI1 nuclear expression reflects the survival of nonsmoking non‐small cell lung cancer patients. Issue 11 (2nd May 2021) - An, Hyo Jung; Kim, Sung Hwan; Yang, Jung Wook; Kim, Min Hye; Baek, Hye Jin; Ryu, Kyeong Hwa; Jeon, Kyung Nyeo; Lee, Chang Sup; Choi, Jun Young; Song, Dae Hyun
Abstract: Background: Smoking‐ and nonsmoking‐associated lung cancers have different mechanisms of carcinogenesis. We divided non‐small cell lung cancer (NSCLC) patients into nonsmoking and smoking groups with the aim of trying to understand the utility of brain‐specific angiogenesis inhibitor 1 (BAI1) expression in the separate groups. Methods: Clinicopathological data were obtained from 148 patients who had undergone surgery for NSCLC of the lung. Tissue microarray blocks were made of samples from NSCLC patients. Two pathologists graded the intensity of BAI1 expression as high or low expression in the cancer cells of patients in the smoking and nonsmoking groups. Results: NSCLC nonsmokers with higher BAI1 nuclear expression had poor disease‐specific survival (DSS) (hazard ratio: 2.679; 95% confidence interval [CI]:1.022–7.022, p = 0.045). The Kaplan–Meier survival curve confirmed that higher BAI1 expression was significantly associated with poor DSS ( p = 0.034) in the nonsmoking group. Conclusions: We divided NSCLC patients into nonsmoking and smoking groups and found that nuclear BAI1 expression was related to patient survival in nonsmoking NSCLC patients. We suggest BAI1 expression as a predictive marker of nonsmoking‐associated NSCLC and recommend that it be evaluated as an AJCC staging criterion in the future. Abstract : Nuclear BAI1 expression was related to patient survival in nonsmoking NSCLC patients. BAI1 expression is expected to be a marker which reveals the mechanism of carcinogenesis in the nonsmoking NSCLC group which can be applied in treatment of lung cancer patients.